Barriers to the identification of possible organ donors among brain-injured patients admitted to intensive care units - Abdul Jabbar bin Ismail; Nor Diyanah Ahmad; Chong Si Ching; Cheah Siew Lean; Tony Tan Beng Keong; Mohd Izzwan Zaini; Cheah Phee Kheng (National Library of Medicine, 2023)
Background: Improving organ donation rates requires better detection of possible organ donors, which in turn necessitates identifying barriers preventing the identification of possible organ donors. The objectives of this study were to determine the actual rate of possible deceased organ donors among nonreferred cases and to identify barriers to their identification as possible donors. Methods: This retrospective observational study used 6 months of data collected from two intensive care units (ICUs). Possible organ donors were defined as patients with a Glasgow Coma Scale score <5 and evidence of severe neurological damage. Barriers that led to the nonidentification of these patients as possible organ donors were also identified. Results: Fifty-six of 819 patients admitted to the ICUs during the study period were detected as possible organ donors, representing a 6.83% possible organ donor detection rate. Nonclinical barriers to the identification of possible organ donors were found to be more significant than clinical barriers (55% vs. 45%, respectively). The most significant nonclinical barrier was an unknown reason, despite patients being medically suitable for deceased organ donation and fulfilling the criteria for possible organ donor classification. Unresolved sepsis was the main clinical barrier. Conclusions: The significant rate of unreferred possible deceased organ donors found in this study reveals the need to increase awareness and knowledge among clinicians of the proper detection of possible donors at an early stage to avoid the loss of possible deceased organ donors, and thereby increase the deceased organ donation rate in Malaysian hospitals.